Desarrollo fenológico del frejol panamito (Phaseolus vulgaris) a base de abono orgánico en Ecuador - Contreras Sarcos, Angelo Steven (2023)
Crops based on chemical treatments are mostly harmful to the soil, but their use is strongly linked to the management given by farmers, therefore it is very difficult to change that fact, hence the importance of exemplifying how other fertilizers can be given better development throughout the stages of a crop, organic fertilizers intervene in this, these fertilizers contain a large amount of vitamins that intervene in a good way both in the fortification of the soil and in the growth of the plant, using chicken manure, manure, whether bovine or pig, or also worm humus, can contribute significantly to a specific crop. Taking the above into account, it can be said that the phenological development of the panamito bean has been strongly linked to the use of chemical agents, so it was concluded that using organic fertilizers contribute better to the phenological character of the crop, such as a good height, greater grain capacity, better color, greater yield in terms of resistance and effectiveness of fruits, a faster plant in development, all thanks to good organic control in said crop.